2007
DOI: 10.1093/ecam/nem062
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Mechanism of Electroacupuncture: Anti‐Injury Effect on Cerebral Function after Focal Cerebral Ischemia in Rats

Abstract: We explored the neurochemical mechanism of electroacupuncture's (EA) protective effect on brain function in focal cerebral ischemia rats, using cerebral ischemia/reperfusion rats established by the middle cerebral artery occlusion (MCAO) method. Adult male Sprague–Dawley rats were randomly divided into four groups: Sham, Sham+EA, MCAO and MCAO+EA. The rats in Sham+EA and MCAO+EA were accepted EA treatment at ‘GV26’ and ‘GV20’ acupoints for 30 min. Electric stimulation was produced by a G-6805 generator and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…This creates further reactive oxygen species generation and cellular injury [57]. This study confirmed that EA improved mitochondrial function in injured tissues [58], and electro-acupuncturing the ST36 acupoint [59] relieved the swelling of mitochondria. On day 28, the contusion group showed mitochondrial changes accompanied by myofibril fracture and atrophy.…”
Section: Discussionsupporting
confidence: 56%
“…This creates further reactive oxygen species generation and cellular injury [57]. This study confirmed that EA improved mitochondrial function in injured tissues [58], and electro-acupuncturing the ST36 acupoint [59] relieved the swelling of mitochondria. On day 28, the contusion group showed mitochondrial changes accompanied by myofibril fracture and atrophy.…”
Section: Discussionsupporting
confidence: 56%
“…EA administered 15 min after occlusion of MCA enhanced the expression of insulin-like growth factor-1, which might be an important mechanism of neuroprotective effects of EA against cerebral ischemia in monkey [4]. Moreover, application of EA immediately after ischemia could increase anti-oxidative activities, thereby reducing neurological deficits in ischemic rats [5], [28]. When EA stimulation was administered immediately after reperfusion, EA attenuated neuronal cell death via regulation of different receptors such as NMDA receptor, and downstream intracellular signaling events inducing phosphatidylinositol 3-kinase (PI3K), Akt and caspase-9 [6], [29], [30].…”
Section: Discussionmentioning
confidence: 93%
“…EA has been recommended as a complementary therapy in the global scope of stroke rehabilitation. Several studies investigating the effectiveness of EA with cerebral ischemia have been conducted, and beneficial neuroprotective effects have been observed [1518]. Both in animal models of cognitive impairment and in patients with deficiencies of learning and memory, some inspiring outcomes of EA have been reported [19, 20].…”
Section: Introductionmentioning
confidence: 99%